The Effect of Virtual Human Rendering Style on User Perceptions of Visual Cues - Stuart, Jacob; Aul, Karen; Stephen, Anita; Bumbach, Michael D.; Lok, Benjamin (Frontiers in Virtual Reality, 2022)
Introduction: Virtual humans have expanded the training opportunities available to healthcare learners. Particularly, virtual humans have allowed simulation to display visual cues that were not previously possible in other forms of healthcare training. However, the effect of virtual human fidelity on the perception of visual cues is unclear. Therefore, we explore the effect of virtual human rendering style on the perceptions of visual cues in a healthcare context. Methods: To explore the effect of rendering style on visual cues, we created a virtual human interface that allows users to interact with virtual humans that feature different rendering styles. We performed a mixed design user study that had undergraduate healthcare students (n = 107) interact with a virtual patient. The interaction featured a patient experiencing an allergic reaction and required trainees to identify visual cues (patient symptoms). The rendering styles explored include a 3D modeled virtual human and an AI-generated photorealistic virtual human. Visual cues were applied using a Snapchat Lens. Results: When users are given a frame of reference (users could directly compare symptoms on both rendering styles), they rated the realism and severity of the photorealistic virtual human’s symptoms significantly higher than the realism of the 3D virtual human’s symptoms. However, we were unable to find significant differences in symptom realism and severity ratings when users were not given a frame of reference (users only interacted with one style of virtual humans). Additionally, we were unable to find significant differences in user interpersonal communication behaviors between the 3D and photorealistic rendering styles. Conclusion Our findings suggest 1) higher fidelity rendering styles may be preferred if the learning objectives of a simulation require observing subtle visual cues on virtual humans and 2) the realism of virtual human rendering style does not necessarily affect participants’ interpersonal communication behaviors (time spent, questions asked).